Ishara : Signs, Symbols and shared Languages. - Sultan, Karim; Albisher, Taiba; Ansari, Saira (Dubai : Alserkal Avenue, 2018)
Al Dabbagh, Amna ; Khorchid, Dina ; Al Qasimi, Farah ; Lee, Founder ; Nasrallah, Nasir ; Qizilbash, Saba ; Al-Mansoori, Salem ; Al Ketbi, Shaika
Tentoonstelling 'Ishara : Signs, Symbols and shared Languages', Concrete, Alserkal Avenue, Dubai, 2018.
Engels
Arabisch
boek
Keywords: Dubai; United Arab Emirates